Neotropical Physoderinae revisited, with description of a new, sexually dimorphic species of Leptophysoderes Weirauch (Hemiptera: Reduviidae) - Davranoglou, L. R.; Hwang, W. S.; Weirauch, C. (Zootaxa, 2015)
The small reduviid subfamily Physoderinae has the greatest species diversity in the Oriental region and Madagascar. Only the two monotypic genera Cryptophysoderes Wygodzinsky and Maldonado and Leptophysoderes Weirauch are currently known from the Neotropical region. We here describe and document a new, sexually dimorphic species of Physoderinae, Leptophysoderes sarapiqui sp. nov. from Costa Rica. The generic diagnosis of Leptophysoderes is modified to accommodate the new species. Females and immatures of Leptophysoderes are documented for the first time.